(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the outcome of topical versus peri-bulbar anesthesia in cataract surgery. Study Design: Randomized control trial. Place and Duration of Study: This study was conducted at the Department of Ophthalmology Unit 1, Jinnah Hospital , /Allama Iqbal Medical College Lahore from January 2013 to January 2014. Materials and Methods: Total 200 patients were divided randomly in two groups by the help of random number table; Group A patients were given topical anaesthesia and group B peribulbar anaesthesia. Pain assessment was done 10 minutes after the anaesthesia by Visual Analogue Scale. All the patients were operated by phacoemulsification technique. On 1st post operated day patient satisfaction was assessed by asking that whether he / she like same anaesthesia in future in terms of yes or no. Results: Out of 100 cases with topical anaesthesia, 51% of the patients experience no pain while 49% were with mild pain but in case of peri-bulbar anaesthesia, 66 % of the patient felt no pain to mild pain. Similarly, in comparison to topical anaesthesia where all of the patients were satisfied with the anaesthesia, up to 72% of patients were satisfied with peri-bulbar anaesthesia. Conclusion: Good level of anaesthesia and more patients’ satisfaction could be achieved by topical anaesthesia as compared to peribulbar anaesthesia.